Specificity of treatment is mandatory in very old patients with hairy cell leukemia - Marisavljević, Dragomir; Marković, Olivera; Živković, Radmila (Vojnosanitetski pregled, 2015)
Introduction. There are only a few available data about hairy cell leukemia (HCL) in very old patients. We presented three very different cases of HCL in very old patients diagnosed in a single center and discussed some epidemiological and therapeutical issues in such patients. Case report. The first patient, 89-year-old, had symptomatic cytopenia and achieved sustained complete remission after cladribine treatment. The second patient, 89-year-old, had asymptomatic disease with stable full blood counts during a 3-year follow-up period in which watch-and-wait policy was adopted. The third patient, 82 years old, had two malignancies (HCL and presumably metastatic colorectal carcinoma) and his only treatment were occasional red blood cell transfusions and symptomatic therapy. Conclusion. The presented illustrative examples confirm individualization of treatment is mandatory in very old patients with HCL.